Polimorfisme Gen Oviductal Glycoprotein-1 pada Oviduk Kambing Peranakan Etawa Penderita Kista Ovarium (OVIDUCTAL GLYCOPROTEIN-1 GENE POLYMORPHISM IN THE OVIDUCT OF ETTAWA CROSSBREED GOATS SUFFERING FROM OVARIAN CYST) - Herawati, Herawati; Ramadhan, Febry Sysdityawan; Oktavianie, Dyah Ayu; Oktanella, Yudit; Oktanella, Yudit (Jurnal Veteriner, 2020)
Ovarian cysts are a disorder characterized by the growth of smooth muscle cells in the ovaries forming like fluid-filled balloons. Oviductal Glycoprotein (OVGP1) is secreted in the oviduct and plays a role in early embryonic development. The incidence of ovarian cysts is thought to affect the level of expression of the OVGP1 gene. The purpose of this study was to determine the potent role of OVGP1 gene as biomarker for detection of ovarian cyst on goats by Polymerase Chain Reaction (PCR) method. The samples used were DNA isolated from normal female PE goat oviduct and goat with follicular ovarian cyst obtained from RPH. The OVGP1 gene identification was performed by PCR method using 5'GACTGCAACCCACACAAGGA-3 forward primer (OVN1 _F) and reverse primer (OVN1_R) 5'GAGAGCAGCACCCACTTTTC-3 ‘. The sequencing of PCR results is done by Sanger method. The gene sequence analysis used the Bioedit and NCBI BLAST programs by comparing the PCR sequence on the follicular ovarian cyst and the normal ovary with the OVGP1 gene of the gene bank NM_001285584.1. The results showed that two normal samples and two samples of follicular cysts had similarities above 90% with OVGP1 gene bank NM_001285584.1. Samples with follicular ovarian cysts indicate a change in nucleotide base sequence due to deletions, insertions, transitions and transversions that affect the amino acid sequence. The arrangement of amino acids on samples with follicular ovarian cysts found an increase in the number of proline (P), threonine (T) and serine (S). In conclusion there is a difference in OVGP1 gene sequences in sample follicular ovarian cysts compared with sample normal ovaries . So the OVGP1 gene potentially can be used as a marker of follicular ovarian cysts.